Incorporation of an Endogenous Neuromodulatory Lipid, Oleoylethanolamide, into Cubosomes Nanostructural Characterization - Younus, Mohammad (Langmuir : the ACS journal of surfaces and colloids, 2016)
Oleoylethanolamide (OEA) is an endogenous lipid with neuroprotective properties and the fortification of its concentration in the brain can be beneficial in the treatment of many neurodegenerative disorders. However, OEA is rapidly eliminated by hydrolysis in vivo, limiting its therapeutic potential. We hypothesize that packing OEA within a nanoparticulate system such as cubosomes, which can be used to target the blood-brain barrier (BBB), will protect it against hydrolysis and enable therapeutic concentrations to reach the brain. Cubosomes are lipid-based nanoparticles with a unique bicontinuous cubic phase internal structure. In the present study, the incorporation and chemical stability of OEA in cubosomes was investigated. Cubosomes containing OEA had a mean particle size of less than 200 nm with low polydispersity (polydispersity index <0.25). Infrared spectroscopy and high-performance liquid chromatography showed chemical stability and the encapsulation of OEA within cubosomes. Cryo-TEM and SAXS measurements were used to probe the influence of the addition of OEA on the internal structure of the cubosomes. Up to 30% w/w OEA (relative to phytantriol) could be incorporated into phytantriol cubosomes without any significant disruption of the nanostructure of the cubosomes. Combined, the results indicate that OEA-loaded cubosomes have the potential for application as a colloidal carrier for OEA, potentially preventing hydrolysis in vivo